2017
DOI: 10.4018/ijagr.2017070101
|View full text |Cite
|
Sign up to set email alerts
|

Least-Cost Pipeline using Geographic Information System

Abstract: Increasing demand for water in Wapuli and its environ led to a proposal to construct a pipeline to link the town to an existing water plant. This paper developed a geospatial model incorporating multi-criteria analysis involving technical factors such as slope, landcover, watercourses, distance to roads and soil types to determine a least-cost path for the pipeline. However, the first least-cost path passes through a tiny sacred grove near Moadani dam, necessitating the generation of a second least-cost path b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Thus, it will be in order to infer that the indigenes in the district are more environmentally friendly and protective of the environment than the technocrats. However, as has been concluded by other studies [7,16,28,29], the protection of the forest and groves may not be purely due to the ecological purposes, but the belief that those areas are the abode of the gods and the ancestral spirits. There is also an argument that the rationale of this belief system is merely the traditional way of protecting the ecosystem.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Thus, it will be in order to infer that the indigenes in the district are more environmentally friendly and protective of the environment than the technocrats. However, as has been concluded by other studies [7,16,28,29], the protection of the forest and groves may not be purely due to the ecological purposes, but the belief that those areas are the abode of the gods and the ancestral spirits. There is also an argument that the rationale of this belief system is merely the traditional way of protecting the ecosystem.…”
Section: Discussionmentioning
confidence: 81%
“…This is not surprising, as these technocrats more or less passed through the same educational system grounded in western values and belief systems that often see indigenous belief systems and practices including the sacred groves as primitive and unscientific and not worth exploring or recognition. In many occasions, such sociocultural and religious values are seen as an obstacle to modernity that must be eliminated [7,27,28]. On the contrary, a study has revealed that indigenes were more willing to have a landfill located closer to watercourses and houses than to the sacred groves since they believe those are the abode of their gods [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost raster data and GIS are widely used to find LCPs for linear infrastructure such as roads [7][8][9], railways [10][11][12], power transmission lines [13,14], pipelines [15,16], and siting wildlife corridors [17,18]. Each transportation mode's important criteria and ranking is different.…”
Section: Related Work and Gapsmentioning
confidence: 99%
“…which is a modification of the model provided by Knaapen et al [45] and is a least-cost model [49,61,62] that represents the cost of an object moving through landscapes of different resistances from a "source" [63]. This method is commonly used in GIS for measuring accessibility [47,64].…”
Section: Urban Construction Land Suitability Regionalization Based Onmentioning
confidence: 99%